TEACHING HOMILETICS AS A PEDAGOGICALLY ORIENTED DISCIPLINE IN THE KYIV THEOLOGICAL ACADEMY (1819-1869) - Tverdokhlib, Tetiana S. (Educological discourse, 2017)
The experience of teaching homiletics as a pedagogically oriented discipline in the Kiev Theological Academy (1819-1869) has been generalized in the article on the basis of the analysis of historical, homiletic and pedagogical literature, archival documents, and materials from periodicals. The content of ecclesiastical eloquence has been revealed, such components as knowledge, abilities and skills, experience of creative activity have been characterized grounding on the study of the “Rules of Church Eloquence”, the textbook “Readings on Church Literature or Homiletics” by Ja. Amfiteatrov. The contribution of Ja. Amfiteatrov to the development of homiletics as a subject and science has been clarified. The general professional level of teachers of church eloquence has been described. The forms of teaching homiletics in the higher theological educational institution in the period under research have been determined and revealed on the basis of the studying historical literature and sources from the funds of the Institute of Manuscripts of the V. I. Vernadskyi National Library of Ukraine (Kyiv). The peculiarities of conducting lectures, practical classes, examinations and writing dissertations have been covered, an important role of practical works in training of future preachers has been established. Two types of examinations having a complex nature (they covered all subjects of the training course, combining verbal questioning and written tasks) have been determined. The problems of homiletics have been found to be rarely considered in the dissertations of students. The dissertation “What determines the persuasiveness of predicant word” by O. Mukhin has been analyzed, since its content is remarkable for the most pedagogical orientation from all dissertations.